TIME AND COST ANALYSIS ON PROCUREMENT OF SUTET 275 Kv 2CCT QUADRUPLE ZEBRA GUMAWANG – GITET LAMPUNG 1 USING TIME COST TRADE OFF METHOD - Adam, Ijaz; Witjaksana, Budi; TJendani, Hanie Teki (Transpublika Publisher, 2024)
Indonesia as an archipelago state is still need an equality development with the intention in achieving the goals to fulfill the requirement of structure and infrastructure. The economy that has experiencing growth, it can be seen with the rising of the demand for supply of electricity power whether it is coming from domestic moreover from industrial usages. Lampung Province, as one of the regions which is in a continuation to develop, requires the support of electric power, which at its peak load reaches 1200 MW, while the capacity of the existing power plant can only produce 700 MW, therefore the construction of a 275 kV Gumawang-Lampung 1 SUTET interconnection network with a capacity of up to 2000 MW was established to meet these requirements. Based on the time schedule which noted that the duration of foundation work started with the excavation, concreting until the reaches of it's curing time in 28 days is 42 days in 2023 December 13th is on try to speed up can be curing in 2023 December 8th, so the schedule tower installation in 2023 December 9th will be on time. Due to this delay, the researcher intends to carry out an acceleration analysis starting with preparing a network diagram using the Microsoft Project software, followed by the crashing process by adding groups of workers and tools of any activities on the critical path. The next step is to calculate the crash cost and cost slope values using the time cost trade off (TCTO) method.